2011
DOI: 10.1039/c1nr10187k
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of partially reduced graphene oxide as room temperature sensor for H2

Abstract: Reduced graphene oxide (RGO) was synthesized under H(2)/Ar treatment from 100 °C to 900 °C. RGO-300 shows excellent sensitivity to H(2) and a dual sensing mode was observed. The balance between the chemical adsorption capacity and electronic conductivity, and the dominance of either electrons or holes are the key factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Partially reduced graphene oxide, however, is known to combine the benefits of GO and rGO [34,35]. In the literature, an optimal balance between chemical adsorption capacity provided by GO and electronic characteristics of rGO has been utilized for gas detection [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partially reduced graphene oxide, however, is known to combine the benefits of GO and rGO [34,35]. In the literature, an optimal balance between chemical adsorption capacity provided by GO and electronic characteristics of rGO has been utilized for gas detection [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have taken advantage of the unique sensing properties of partially reduced graphene oxide (prGO) [27,28]. Neat GO readily interacts with gaseous analytes, thanks to the presence of oxygen-containing functional groups [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of attention is paid to development of the technology of hydrogen energetic fuel cells [3], which makes the monitoring of the concentration of hydrogen necessary. Hydrogen is an explosive gas (at a concentration of 4% to 75% in air [4,5]).…”
Section: Introductionmentioning
confidence: 99%
“…The properties of sensor structures depend (among others) on the gas sensing layers. Sensors based on carbon nanostructures as sensing layers are characterized by low working temperature [3]. In literature much attention is devoted to sensors with carbon nanotubes [9], graphene [10][11][12][13], graphene oxide and reduced graphene oxide [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Particularly, reduced graphene oxide (reduced graphene oxide) have been considered as a promising gas sensing material for detection of gases at room temperature. [19][20][21][22][23][24] Gu et al found that In 2 O 3 -graphene nanocomposite exhibited high sensitivity to NO 2 at room temperature. 25 Deng et al synthesized reduced graphene oxide conjugated Cu 2 O nanowire mesocrystals which exhibit excellent NO 2 sensing performance.…”
Section: Introductionmentioning
confidence: 99%